Sistem Reporting Benefit Karyawan PT Great Giant Pineapple Berbasis Web dengan Framework CodeIgniter 4 - Muhaqiqin Muhaqiqin; Dita Faradila; Ridho Sholehurrohman; Rahman Taufik; Igit Sabda Ilman; Wartariyus (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
An information system is a combination of human resources, data, information technology, and policies/procedures that are regularly integrated to solve business problems and achieve organizational goals. Information systems are also needed in the company's operational activities. An example can be applied to the process of applying for employee benefits. In this research created a system that is used for the process of submitting website-based employee benefits. This system helps HR Service employees to carry out the process of applying for benefits employees of PT Great Giant Pineapple. This system is tested functionally. Based on functional testing it is known that the system meets the required functions.